Effects of digestate co-composting on curing phase of composting. (September 2022) - Arab, Golnaz; Razaviarani, Vahid; McCartney, Daryl
Abstract: The effects of adding polished digestate (8-day aerated digestate) into the curing phase of composting was investigated. The polished digestate was mixed with a 30-day composted OFMSW, introduced to eight composters with different mixing ratios and monitored for 100 days. Monitored parameters were temperature, mass changes, total solids, organic matter, pH, and electrical conductivity. Stability and maturity endpoints were also quantified by running respirometry, C:N ratio, NH4 :NO3 ratio, and Solvita® tests. The results showed that co-composting of polished digestate and 30-day composted OFMSW did not notably improve the overall composting performance and it decreased when the digestate portion increased. This could be due to the excess aeration of the digestate and/or an unsuitable inoculation time. Over-aeration could result in the volatilization of ammonia and loss of nitrogen. There are two speculations: first, the inoculum consortia might be outcompeted by the indigenous microorganisms. Second, substrate could become a limiting factor. Graphical abstract: Unlabelled Image Highlights: Co-composting of polished digestate and composted OFMSW was investigated. Overall co-composting performance did not notably improve. Over-aeration of digestate resulted in the volatilization of ammonia. Unsuitable inoculation time could be a reason for not detecting improvement.